A2.33 Citrullinated self antigen-specific blood B cells carry cross-reactive immunoglobulins with effector potential. (24th February 2016) - Titcombe, PJ; Amara, K; Barsness, LO; Zhang, N; Krishnamurthy, A; Shmagel, A; Hansson, M; Israelsson, L; Sahlström, P; Giacobbe, L; Catrina, AI; Gillespie, EC; et al.
Abstract : Background and objectives: Presence of autoantibodies targeting citrullinated proteins (ACPA) and clinical response from anti-CD20 Rituximab therapy indicate a critical role for B cells in rheumatoid arthritis (RA). Due to the difficulty of reliably tracking rare B cells with a defined specificity, the composition of the autoreactive B cell repertoire contributing to ACPA + RA has not been analysed. We previously developed a tetramer enrichment strategy for capturing autoreactive B cells. We now employ cyclic citrullinated peptide (CCP) tetramers for cloning and expressing citrulline-specific immunoglobulin (Ig) from single blood B cells in RA. Materials and methods: We analysed B cells specific for two previously described CCP, which are citrullinated epitopes from human filaggrin (Cfc1) and alpha-enolase (CEP-1). Antigen-specific B cells were detected by flow cytometry – with fluorescent CCP tetramer for citrulline-specific capture and non-citrullinated peptide decoy tetramer for distinguishing B cells that bind irrelevant epitopes on the tetramer complex. Tetramers were subsequently used to sort single B cells from RA patient (n = 3) blood. Reverse transcription-PCR generated Ig cDNA from the cells. Ig was amplified, cloned, and expressed as monoclonal antibody (mAb). Results: Single B cells sorted by either CCP tetramer (Cfc1 or CEP-1) from RA patients' peripheral blood have highly mutated Ig sequences and show preferential use of the VH4 gene family. When expressed as mAb, 9 of 25 tetramer-sorted clones demonstrated high reactivity towards the targeted CCP epitope, as opposed to 0 of 21 randomly selected memory B cells isolated from the same patient samples. All of the highly citrulline-specific clones further exhibited cross-reactivity to citrullinated epitopes from other proteins and unique binding patterns to these autoantigens on peptide array. The mAb generated from tetramer-selected cells also induced osteoclastogenesis and bone erosion in vitro . Conclusions: Single B cells selected by CCP tetramers have highly mutated Ig sequences and receptors with citrulline-specific reactivity. Efficient isolation of mAb clones from the autoreactive B cell repertoire by this strategy will be used to better understand the pathogenesis of autoimmunity. By re-engineering the expressed Ig Fc domain towards blocking or immunosuppressive functions, mAb with defined disease-associated specificities could also offer intriguing possibilities in targeted therapeutic design for RA and other conditions.